Overexpression and evaluation of an antimicrobial peptide from Heuchera sanguinea (Hs-AFP1) for inhibition of fungal pathogens in transgenic tabacco - De Beer, Abre (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2002.